2010
DOI: 10.1177/1545968310385126
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Versus Focal Cortical Stimulation to Enhance Motor Function and Motor Map Plasticity in a Rodent Model of Ischemia

Abstract: The results indicate that although both focal and distributed forms of CS/RT promote motor map reorganization only the distributed form of CS/RT enhances motor performance with rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 50 publications
3
45
2
Order By: Relevance
“…10,13,36,37,39,41 As seen in Figure 3, we found that motor RT significantly increased the total area of wrist representation in the injured cortex elicited with £100 lA, inclusive of RMC and CMC (F (1,20) = 6.193; p = 0.02), compared to NoRT. The overall increase in wrist representation was mainly driven by a significant expansion of wrist in the RMC (Fig 3B; F (1,20) = 7.69; p = 0.012), although there was an nonsignificant enlargement of wrist representation in CMC, as well (F (1,20) = 2.913; p = 0.104).…”
Section: Intracortical Microstimulation Motor Mapsupporting
confidence: 56%
“…10,13,36,37,39,41 As seen in Figure 3, we found that motor RT significantly increased the total area of wrist representation in the injured cortex elicited with £100 lA, inclusive of RMC and CMC (F (1,20) = 6.193; p = 0.02), compared to NoRT. The overall increase in wrist representation was mainly driven by a significant expansion of wrist in the RMC (Fig 3B; F (1,20) = 7.69; p = 0.012), although there was an nonsignificant enlargement of wrist representation in CMC, as well (F (1,20) = 2.913; p = 0.104).…”
Section: Intracortical Microstimulation Motor Mapsupporting
confidence: 56%
“…While the relationship between cortical movement representations and behavior is not simple (Boychuk et al, 2011), decreases or increases in motor map size are often accompanied by deficits in fine motor control. Abnormal motor maps and decreased skilled reaching performance have previously been observed following cortical ischemia , repeated seizures , DA depletion (Brown et al, 2011), and high-frequency stimulation intended to saturate cortical excitability (Henderson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, although cytoarchitectonic analysis of human precentral fMRI functional magnetic resonance gyrus suggests its volume is 100 times larger than that of rodents, the stimulation contact area in humans is only 4-7 times greater [30]. Is the dramatically variable success of animal versus clinical studies simply a function of a disproportionately smaller percentage volume targeted in humans?…”
Section: Methodologicalmentioning
confidence: 99%
“…Their contribution evidently emerges from substantial (~60 %) and independent projections to corticospinal pathways [56], extensive reciprocal connections with M1 [57], and dense transcallosal connections with their homologues [57]. Although we currently explore how stimulating higher motor areas potentiates vicariation [33], a recent rodent model by Boychuk et al [30] may offer some translational insight. They have discussed that stimulating distributed regions in the periphery of ipsilesional motor cortices is more efficacious than focal stimulation in the interior of M1.…”
Section: Alternate Substrates and Their Role In Recovery: Cortical Sumentioning
confidence: 99%